Effect of Heavy Metals on Plant Growth and Ability to use Fertilizing Substances to Reduce Heavy Metal Accumulation by Brassica Juncea L. Czern (Global Journal of Science Frontier Research, 2015)
Heavy metal pollution in soil and water is a global environmental concern. In Vietnam, accumulation of heavy metals in soil, water and plant biomass has been widely reported. Cultivation of crops on contaminated sites may result in both growth inhibition and tissue accumulation of heavy metals with resulting possible risks to humans health. In this paper, plant growth inhibition and accumulation of Cu, Pb and Zn by Brassica juncea L. Czern are studied in pot experiments.
Keywords: brassica juncea; heavy metal accumulation; lime; phosphate; sawdust